Photon scattering by an electric field in noncommutative spacetime - D'Ascanio, Daniela (2024)
As is known, the existence of a small noncommutativity between coordinates would generate nonlocal selfinteractions in the electromagnetic theory. To explore some consequences of this effect on the propagation of photons we consider Moyal space half-filled with a static and homogeneous electric field and analyze electromagnetic fluctuations on top of this step-like background. Both the localization of photons and the possibility of photon production by strong electric fields are addressed. Several aspects of the Klein paradox in this setup are discussed as well.